Key to conifer-infesting species of Lepidosaphes Shimer worldwide (Hemiptera: Coccoidea: Diaspididae), with descriptions of two new species and a redescription of L. pallidula (Williams) - Miller, Douglass R.; Williams, Douglas J.; Davidson, John A. (Zootaxa, 2006)
Two new species of Lepidosaphes are described, L. caribaeae Williams and Miller from Trinidad and Jamaica and L. murreeana Williams and Miller from Pakistan. Lepidosaphes pallidula (Williams), a non-conifer infesting species, is redescribed so that it can be distinguished from L. pallida (Maskell), a species commonly detected on conifers. A dichotomus key is presented for the identification of the adult females of the 25 species of Lepidosaphes that occur on conifers worldwide and a matrix is provided containing 23 characters considered important in distinguishing the 25 conifer-infesting species.